Revitalization of the Prophet's Da'wah in the Era of Social Media - Sarah Apiani; Lina Pusvisasari; Zahron Nafisah (Penerbit Hellow Pustaka, 2025)
Da'wah is an obligation for every Muslim to spread the teachings of Islam with wisdom and prudence. In the fast-paced and globalized era of social media, the spirit of Prophet Muhammad’s da'wah must be revitalized with relevant and innovative approaches. This journal aims to analyze the role of young people in revitalizing the da'wah of Prophet Muhammad by utilizing digital platforms. Beginning with the urgency of understanding the history of the Prophet’s da'wah, this journal explores communication strategies inspired by his letters. The challenges of globalization and the influence of social media on the mindset of Muslim youth are discussed as both obstacles and opportunities for modern da'wah. The youth hold significant potential to adapt classical da'wah values into effective digital communication while adhering to ethical principles and the etiquette of da'wah. The conclusion emphasizes that a combination of historical understanding, creativity, and wise use of technology can enhance the competitiveness of Islamic da'wah amidst contemporary challenges.